Analisis Pengaruh Kepemilikan Asing Terhadap Volatilitas Return Saham, Volume Perdagangan, Dan Risiko Saham Di Indonesia - Desy Febriana Sari; Hersugondo Hersugondo (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2021)
This study aims to determine the effect of foreign ownership on volatility, trading volume, and stock risk in companies listed in the LQ45 index on the Indonesia Stock Exchange. The research period used was 2018-2020. Samples were taken using a purposive method and obtained a total sample of 21 companies. The data used are secondary data. The data analysis method used is multiple linear regression with a level of significance of 0.05. The results of this study indicate that: Foreign ownership has a positive and significant effect on stock return volatility, foreign ownership has no significant effect on trading volume, foreign ownership has a positive and significant effect on stock risk.